ANALISIS FAKTOR YANG MEMPENGARUHI PERILAKU ORGANISASI PERAWAT DI RUMAH SAKIT UMUM DAERAH KABUPATEN LUWU - Hairuddin Safaat; Tn. Jumadil (Voice of Midwifery, 2018)
The needs of nurses who have the category of "good citizen" is the main concern that can not be ignored by management because it will have a positive impact on the organization.The purpose of this research is to analyze the influence  of workload, job satisfaction and organizational commitment to Organizational Citizenship Behavior nurses. The research involved 104 implementer nurses. Data excavation techniques used questionnaires and interviews. Data were analyzed by regression analysis, t test, F test and coefficient of determination.The result of the research at the 5% significance level shows that: Workload has positive effect not significant to OCB nurse (regression coefficient: 0.116, p value: 0.245). The variables that give positive and significant influence to the nurse OCB are job satisfaction (regression coefficient: 0,226 and p value: 0,022) and organizational commitment (regression coefficient: 0,253 and p value: 0,012). Workload, job satisfaction and organizational commitment simultaneously give positive and significant influence to OCB nurse (F arithmetic: 4.836) with sig value: 0,003). Organizational commitment was the most dominant variable significantly influence the organizational citizenship behavior of nurses in the context of nurses in Batara Guru regional hospital, Luwu regency. Keywords : Work load, job satisfaction, organizational commitment, Organizational Citizenship Behavior